Polo mar van as sardiñas y sus traducciones - Domínguez Pérez, Mónica (Madrygal. Revista de Estudios Gallegos, 2008)
It can be said that Galician children’s literary system was born during the sixties. The first original book published in Galicia for those days was Polo mar van as sardiñas, a picture book written by Xohana Torres, published at the same time in the four official languages of Spain. In this paper the book is presented from different perspectives: its genesys, main features, authors… But the translations are enfazised, taking into account their norms and features of diffusion and recepcion. So, we can make evident the importance of this picture book, pioneer in Galician children’s literature and its delegate in neighborgh literatures. Nevertheless, the recent recovery of the text in Galician contrasts with the forgetness in which it has fallen for the agents of the other literatures.